2019
DOI: 10.2991/jegh.k.191009.001
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Severe Pneumonia According to WHO 2005 Criteria Definition Among Children <5 Years of Age in Thai Binh, Vietnam: A Case–Control Study

Abstract: Vietnam is one of the 15 countries where the prevalence of child pneumonia is highest. It is a major cause of admission in pediatric hospitals. However, little is known on the burden of severe pneumonia and their risk factors in children <5 years of age in Vietnam. A case-control study was conducted among children aged 2-59 months presenting with pneumonia at the Pediatric Provincial Hospital of Thai Binh. Cases were children with severe pneumonia while controls included those with non-severe pneumonia as defi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 26 publications
0
12
0
2
Order By: Relevance
“…Cakupan vaksin yang tinggi memungkinkan kekebalan kelompok (herd immunity) untuk anak yang tidak divaksinasi. 24,25 Berbeda dengan hasil yang ditemukan oleh Hoang dkk, 26 malnutrisi tidak memiliki hubungan bermakna dengan pneumonia berat dalam penelitian ini. Hubungan tersebut dapat disebabkan oleh perbedaan proporsi yang besar.…”
Section: Pembahasanunclassified
“…Cakupan vaksin yang tinggi memungkinkan kekebalan kelompok (herd immunity) untuk anak yang tidak divaksinasi. 24,25 Berbeda dengan hasil yang ditemukan oleh Hoang dkk, 26 malnutrisi tidak memiliki hubungan bermakna dengan pneumonia berat dalam penelitian ini. Hubungan tersebut dapat disebabkan oleh perbedaan proporsi yang besar.…”
Section: Pembahasanunclassified
“…Moreover research stated that history of exposure to cigarette smoke increase risk 3.87 times causing severe pneumonia in children less than 5 years old (95% CI 1.62-9.23; p=0.008) [16]. Another similar study found that children who were exposed to indoor cigarette smoke either during infancy or childhood were at increased risk for respiratory distress (adjusted OR 1.23; 95% CI 1.03-1.47) [25].…”
Section: Discussionmentioning
confidence: 96%
“…A report data stated that the highest prevalence of pneumonia was found in the age group 1 month to 4 years as much as 2.1%, followed by ages 5-14 years as much as 1.7% and ages 15-24 years as much as 1.8% [15]. In addition, Hoang et al ( 2019) also stated the highest prevalence of pneumonia was found in the age group 2 months -<12 months as much as 80.7%, followed by the age group 12-24 months as much as 15.7%, age 34-36 months as much as 1.2%, and 36-59 months as much as 2.4% [16].…”
Section: Discussionmentioning
confidence: 99%
“…The hospital authorities can arrange proper diagnosis and management of all patients and suspected cases accordingly. Out of hospital admitted patients, the most common case is ARI and Diarrhoea (Hoang et al, 2019). Most of them treated accordingly to take weeks to recover completely.…”
Section: Discussionmentioning
confidence: 99%